A review of dietary and non-dietary exposure to bisphenol-A - Geens, Tinne; Aerts, Dominique; Berthot, Carl; Bourguignon, Jean-Pierre; Goeyens, Leo; Lecomte, Philippe; Maghuin-Rogister, Guy; Pironnet, Anne-Madeleine; Pussemier, Luc; Scippo, Marie-Louise; Van Loco, Joris; Covaci, Adrian (Food and chemical toxicology, 2012)
► Food and non-food sources of BPA are reviewed. ► Overall exposure to BPA is dominated by food sources. ► Overall exposure to BPA can be reliably estimated by human biomonitoring of urine. ► Alternatives for polycarbonate should be thoroughly toxicologically tested. Due to the large number of applications of bisphenol-A (BPA), the human exposure routes are multiple. We aimed to review shortly the food and non-food sources of BPA, and to evaluate their contribution to the human exposure. Food sources discussed here include epoxy resins, polycarbonate and other applications, such as paperboard and polyvinylchloride materials. Among the non-food sources, exposures through dust, thermal paper, dental materials, and medical devices were summarized. Based on the available data for these exposure sources, it was concluded that the exposure to BPA from non-food sources is generally lower than that from exposure from food by at least one order of magnitude for most studied subgroups. The use of urinary concentrations from biomonitoring studies was evaluated and the back-calculation of BPA intake seems reliable for the overall exposure assessment. In general, the total exposure to BPA is several orders of magnitude lower than the current tolerable daily intake of 50μg/kgbw/day. Finally, the paper concludes with some critical remarks and recommendations on future human exposure studies to BPA.